The Role of Organizational Commitment in Moderating the Influence of Organizational Culture on Employee Performance - Dafiana, Erla; Sutianingsih, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Human resources are one of the most important assets that have a direct impact on an organization. There are several things that can affect an organization in achieving high-quality employee performance. Both the company's culture and its employees' dedication to the company fall under this category. Through the moderating effect of organisational commitment, this study seeks to elucidate how organisational culture affects employee performance. The 837 people who work at Pandang Arang Hospital in Boyolali Regency were the subjects of this study. In order to ensure conformity, the computation results could be rounded using the Slovin algorithm, and a relaxation percentage of 5% was employed to select the sample. It has been determined that 275 employees will make up the sample set. The study's findings indicate that 1) organisational culture positively impacts employee performance and 2) organisational commitment enhances the correlation between OCP and performance.